Upaya Penanganan Hipertensi dalam Kesehatan Masyarakat - Tata Azzalia Khairan (Lembaga Pengembangan Kinerja Dosen, 2026)
According to the WHO and the Ministry of Health, hypertension is defined as blood pressure ≥ 140/90 mmHg, consistent with the ESC/ESH guidelines. Hypertension is one of the leading causes of premature death worldwide. Symptoms experienced by patients with hypertension include headaches, sweating, palpitations, snoring, daytime sleepiness, muscle weakness, cramps, and cardiac arrhythmia. Clinical manifestations of hypertensive urgency include elevated blood pressure, severe headache, anxiety, and shortness of breath. Mrs. M, a 68-year-old woman, came to the Samudera Community Health Center complaining of a headache that had worsened approximately 3 days ago. The headache is felt at the back of the head, feeling heavy, and sometimes radiates throughout the entire head. The patient also describes the headache as throbbing. The headache was exacerbated when the patient could not sleep, consumed salty foods, and did not take her medication regularly. The headache subsides slightly when the patient takes medication and sleeps with their head elevated. The patient reported that the symptoms were also accompanied by nausea, dizziness, palpitations, and an inability to sleep at night. The patient has been diagnosed with hypertension for approximately 5 years. On physical examination, the patient’s blood pressure was 190/100 mmHg. The patient was advised to adopt a healthy diet by reducing salt intake. The patient was also prescribed the following medications: Captopril 25 mg twice daily, Amlodipine 5 mg once daily, Paracetamol 500 mg three times daily, and Domperidone 10 mg twice daily, to be taken as needed.